Solar energy storage in German households: profitability, load changes and flexibility. (November 2016) - Kaschub, Thomas; Jochem, Patrick; Fichtner, Wolf
Abstract: The developments of battery storage technology together with photovoltaic (PV) roof-top systems might lead to far-reaching changes in the electricity demand structures and flexibility of households. The implications are supposed to affect the generation mix of utilities, distribution grid utilization, and electricity price. Using a techno-economic optimization model of a household system, we endogenously dimension PV system and stationary battery storage (SBS). The results of the reference scenario show positive net present values (NPV) for PV systems of approx. 500–1, 800 EUR/kWp and NPV for SBS of approx. 150–500 EUR/kWh. Main influences are the demand of the households, self-consumption rates, investment costs, and electricity prices. We integrate electric vehicles (EV) with different charging strategies and find increasing NPV of the PV system and self-consumption of approx. 70%. With further declining system prices for solar energy storage and increasing electricity prices, PV systems and SBS can be profitable in Germany from 2018 on even without a guaranteed feed-in tariff or subsidies. Grid utilization substantially changes by households with EV and PV-SBS. We discuss effects of different incentives and electricity tariff options (e. g. load limits or additional demand charges). Concluding, solar energy storage systems will bring substantial changes to electricity sales. Highlights: Domestic photovoltaics (PV) and storage systems are techno-economically analyzed. PV & storage are profitable in the medium term due to high self-consumption rates. Controlled electric vehicle charging improves load flexibility and self-generation. External procurement of electricity drastically changes and decreases to 48–58%. Dynamic tariffs e. g. with load limits or demand charges incentivize load shifting.